2005
DOI: 10.2174/0929866053005845
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of pH, Cu+2 and Sheet Breakers on Aggregation of Amyloid Peptides

Abstract: The study explores in vitro by circular dichroism and mass spectrometry the effects of pH, Cu+2 ions and sheet-breakers on the secondary structures and self-aggregation of beta-amyloid peptides [Abeta43, Abeta42 and Abeta40] of Alzheimer's disease. Within pH 5.4-7.3, more sheet structures and aggregates containing up to 11 peptide units were observed. Cu+2 ions led to oxidative degradation or aggregation depending on its concentration and time of incubation. beta-sheet breakers can reverse the self-aggregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Analogously, although MALDI-TOF and ESI/MS could be very useful to characterize a newly synthesized decapeptide with an amino acid sequence contained in the full-length Ab, CD, as well as AFM investigations, were necessary to study the influence of the environmental conditions (the presence of metal ions or sodium dodecyl sulfate (SDS)) on the secondary structure of the peptide to confirm a morphological change before and after copper treatment and/or SDS in the surface packing of the peptide shell (Murariu, Dragan, & Drochioiu, 2007). Similar results have also been obtained for the full-length Ab by coupling MS and CD, because it was found that Cu 2þ led to oxidative degradation or aggregation, depending on its concentration and time of incubation, whereas b-sheet breakers can reverse the selfaggregation process (Beking et al, 2005).…”
Section: B Other Analytical Approachessupporting
confidence: 64%
“…Analogously, although MALDI-TOF and ESI/MS could be very useful to characterize a newly synthesized decapeptide with an amino acid sequence contained in the full-length Ab, CD, as well as AFM investigations, were necessary to study the influence of the environmental conditions (the presence of metal ions or sodium dodecyl sulfate (SDS)) on the secondary structure of the peptide to confirm a morphological change before and after copper treatment and/or SDS in the surface packing of the peptide shell (Murariu, Dragan, & Drochioiu, 2007). Similar results have also been obtained for the full-length Ab by coupling MS and CD, because it was found that Cu 2þ led to oxidative degradation or aggregation, depending on its concentration and time of incubation, whereas b-sheet breakers can reverse the selfaggregation process (Beking et al, 2005).…”
Section: B Other Analytical Approachessupporting
confidence: 64%
“…The capability to cause membrane fusion and to promote lipid reorganization was already detected for the C-terminal domain of the amyloid peptide Aβ (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). 30 Our investigation extends this property to the more relevant natural form of Aβ.…”
Section: Discussionmentioning
confidence: 94%
“…In our previous work, we have applied neutron diffraction to stacked lipid multilayers to localize a selectively deuterated amino acid of the short Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Membrane perturbation and peptide insertion in the hydrophobic core were our main results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular note, b-sheet breakers constitute a new class of drugs that are designed to specifically bind amyloid b peptide by blocking and/ or reversing the misfolding process. [58,59,61,62] Several inhibitors of Ab fibril formation have been reported, [11,[63][64][65][66][67][68][69][70][71] however, protein-protein interactions are exceedingly difficult to inhibit. Small molecules lack sufficient steric hindrance to prevent interactions between large peptide surfaces.…”
Section: Ab42 Self-aggregation Inhibition Studiesmentioning
confidence: 99%